Influences of Cross-Border Mobility on Tuberculosis Diagnoses and Treatment Interruption Among Injection Drug Users in Tijuana, Mexico - Deiss, Robert (American Public Health Association, 2009)
Objectives. We sought to identify correlates of reported lifetime diagnoses of TB among injection drug users in the border city of Tijuana, Mexico. Methods. Injection drug users in Tijuana were recruited into a prospective cohort study during 2006 and 2007. We used weighted multivariate logistic regression to identify correlates of TB diagnoses. Results. Of the 1056 participants, 103 (9.8%) reported a history of TB, among whom 93% received anti-TB medication and 80% were diagnosed in the United States. Treatment was prematurely halted among 8% of patients; deportation from the United States was the cause of half of these treatment interruptions. History of travel to (odds ratio [OR] = 6.44; 95% confidence interval [CI] = 1.53, 27.20) or deportation from (OR = 1.83; 95% CI = 1.07, 3.12) the United States and incarceration (OR = 2.20; 95% CI = 1.06, 4.58) were independently associated with a reported lifetime diagnosis of TB. Conclusions. Mobility and migration are important factors in identifying and treating TB patients diagnosed in the US–Mexico border region. Strengthening capacity on both sides of the border to identify, monitor, and treat TB is a priority.